Borderline personality disorder is associated with lower confidence in perception of emotional body movements - Kaletsch, Morten; Krüger, Britta; Pilgramm, Sebastian; Stark, Rudolf; Lis, Stefanie; Gallhofer, Bernd; Zentgraf, Karen; Munzert, Jörn; Sammer, Gebhard (Frontiers in Psychology, 2014)
Much recent research has shown that personality disorders are associated with an altered emotion perception. Whereas most of this research was conducted with stimuli such as faces, the present study examined possible differences in the perception of emotions expressed via body language and body movements. 30 patients with borderline personality disorder and 30 non-patients observed video scenes of emotional human interactions conveyed by point–light displays, rated the depicted valence, and judged their confidence in this rating. Patients with borderline personality disorder showed no altered emotion perception (i.e., no biased perception in either a negative or a positive direction). They did not perceive and evaluate depicted emotions as being more extreme than healthy controls. However, patients with borderline personality disorder showed less confidence in their perception of depicted emotions, especially when these were difficult to identify. The findings extend insights on altered emotion perception in persons with borderline personality disorder to include the field of body movements.